선택적 CSR과 외부주주의 감시에 대한 연구 - 최향미(Hyang-Mi Choi); 임병권(Byung-Kwon Lim); 안지영(Ji-Young Ahn) (무역연구, 2024)
Purpose – This study seeks to explore the impact of outside shareholders on CSR, and discuss how outside shareholders interact with corporate ownership structure to affect CSR. Design/Methodology/Approach – Using longitudinal data from 297 publicly listed companies in Korean large business groups, the study examined the direct and interaction effects of outside shareholders and corporate ownership structure on CSR. It focused on the impact of institutional stockholders holding 5% or more of the equity shares and foreign investors on corporate governance. Findings – While institutional investors do not significantly affect CSR, foreign investors have a positive impact and moderate the effects of corporate ownership structure on CSR. They respectively moderate the positive impact of controlling shareholder ownership and the negative impact of control-ownership disparity on CSR. These findings suggest that foreign investors play a role as independent monitors in aligning corporate governance with CSR objectives in large Korean business groups. Research Implications – The findings highlight the possibility of CSR being exploited for private benefits by controlling shareholders without effective corporate governance. This study emphasizes the need for monitoring and balanced oversight in reducing conflicts over CSR, suggesting the importance of outside shareholder engagement in corporate governance. It posits that outside shareholders, particularly foreign investors, are instrumental in fostering responsible corporate governance and CSR practices. KCI Citation Count: 1